2018
DOI: 10.1111/cea.13160
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term effect of outdoor mould spore exposure on prescribed allergy medication sales in Central France

Abstract: The association between prescribed daily sales of oral antihistamines with topical treatment sales is associated with temporal changes to Cladosporium and Aspergillus-Penicillium in the whole population. When the influence of age and sex was considered, these two moulds contributed to prescribed medication sales only in the male general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In temperate climates, peaks of fungal counts are observed in the summer, as in the case of Cladosporium spp. [31], or spore concentrations can also differ between days or years, as previously described for Alternaria spp. [32].…”
Section: Introductionmentioning
confidence: 81%
“…In temperate climates, peaks of fungal counts are observed in the summer, as in the case of Cladosporium spp. [31], or spore concentrations can also differ between days or years, as previously described for Alternaria spp. [32].…”
Section: Introductionmentioning
confidence: 81%
“…This study was entirely anonymous and so approval from the French Ethics Committee was not required. Mould samples were collected daily from mid‐February to early October, as described previously [3 ]. Molds and pollens were sampled on the rooftop of a building of the University Hospital, with no nearby buildings obstructing air circulation.…”
Section: Methodsmentioning
confidence: 99%
“…Environmental exposure post‐pregnancy has also been surveyed in Clinical and Experimental Allergy. Caillaud et al report short‐term effect of outdoor mould spore exposure on prescribed allergy medication sales in Central France. Quite unexpectedly, Brough et al found that higher levels of environmental exposure to peanut in the first few months of life appeared to increase the probability of developing school‐age peanut sensitization in atopic children.…”
Section: Epidemiologymentioning
confidence: 99%